Maintenance management at basement car parking space in commercial building / Mohamad Zulhilmi Abu Bakar - Abu Bakar, Mohamad Zulhilmi (Faculty of Architecture,Planning and Surveying, 2015)
Maintenance Management represents a tool for continuous and sustainable improvements and allows for the efficient operation and maintenance of the buildings. Until very recent, Maintenance Management (MM) was not common in Malaysia. Designers used to design all types of buildings without consideration for the Maintenance Management requirements. Unfortunately, this has lead to various problems especially for commercial buildings, which require special Maintenance Management considerations during the different phases of the Facility starting from the Conceptual Planning and Design phases until the Operation and maintenance phase During the last decade, construction development and urban planning have been undergoing a new leap, tremendous changes, and concept improvement. Developers have felt the significance of considering (MM) during the life-cycle of the facility in order to protect their assets and to achieve users’ satisfaction. The government has also assisted in this notion by adequately planning business parks with all required services and infrastructure. Tens of new office buildings have been developed during this period. This paper aims to identify the Maintenance Management at basement car parking space in commercial buildings, which it case area in Shah Alam Selangor. A survey has been conducted on number of commercial buildings to monitor and depict the opinion of its occupants on the building design and services. Analysis of this survey illustrates the pros and cons of the buildings’ functions and performance. Finally, the paper demonstrates the impact of maintenance management and its significant role in improving the commercial building performance